2021
DOI: 10.1186/s12872-021-02059-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced plasma level of basic fibroblast growth factor is associated with incomplete device endothelialization at six months following left atrial appendage closure

Abstract: Objectives To investigate whether inflammatory and growth factors (IGFs) were associated with incomplete device endothelialization (IDE) at 6 months after successful left atrial appendage closure (LAAC). Background IDE after LAAC is correlated with device-related thrombus (DRT) formation and subsequent thromboembolic events. However, biomarkers for early detection of IDE remain lacking. Methods Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Regarding the exploration of additional biomarkers capable of identifying incomplete device endothelialization (IDE) and potential peri-device leakage (PDL), Xu et al [31] conducted a study involving 55 patients. Their investigation delved into inflammatory and growth factors (IGFs), encompassing plasma levels of specific IGFs, including basic fibroblast growth factor (bFGF), platelet-derived growth factor (PDGF), stromal cell-derived factor (SDF)-1a, transforming growth factor (TGF)-β1, vascular growth factor receptor-1 (VEGF-R1), and von Willebrand factor (vWF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the exploration of additional biomarkers capable of identifying incomplete device endothelialization (IDE) and potential peri-device leakage (PDL), Xu et al [31] conducted a study involving 55 patients. Their investigation delved into inflammatory and growth factors (IGFs), encompassing plasma levels of specific IGFs, including basic fibroblast growth factor (bFGF), platelet-derived growth factor (PDGF), stromal cell-derived factor (SDF)-1a, transforming growth factor (TGF)-β1, vascular growth factor receptor-1 (VEGF-R1), and von Willebrand factor (vWF).…”
Section: Discussionmentioning
confidence: 99%
“…Among these six IGFs, solely the plasma level of bFGF exhibited a significant decrease in patients exhibiting IDE. Notably, employing a cut-off value of 440.52 pg/mL (with a sensitivity of 76.5% and a specificity of 78.9%), Xu et al [31] identified lower bFGF levels as an independent factor associated with IDE. This finding was substantiated by a multivariate logistic regression model [31].…”
Section: Discussionmentioning
confidence: 99%
“…LAAC procedure and anticoagulation regimen LAAC procedure was performed under uoroscopy and trans-esophageal echocardiography guidance by the standard technique described previously [19]. In brief, intravenous heparin was administered following transseptal puncture and introduction of delivery system to the left atrial appendage.…”
Section: Study Populationmentioning
confidence: 99%